PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MATERI GEOMETRI BERBASIS TEORI BELAJAR VAN HIELE UNTUKMENGEMBANGKAN KARAKTER SISWA KELAS VII1 SMP 2 BULUPODDO - Kamaruddin, Rahmat; Rahman, Abdul; Djadir, Djadir (MaPan : Jurnal Matematika dan Pembelajaran, 2014)
This research is research and development which aimed at generating mathematics learning device of geometry based on Van Hiele learning theory to improve character of students that meet the criteria of valid, practical, and effective. The desired product in this study was: a valid, practical, and effective learning device. The product konsists of four components: lesson plan, student books, students work sheet, and test of learning outcomes. Process of learning device development using model 4-D thiagarajan which consists of 4 stages: define, design, develop, and disseminate. The results showed that the learning device developed is valid, practical, and effective based on the assessment of validator and the results of trials conducted. Validity of teh device was measured by assessment validation results of the experts who meet the criteria of validity, namely (1) lesson plans, (2) Students books, (3) Student’s work sheet, (4) test of leraning outcames with the content validity of each more than 75% or V > 75%. It indicated that thr four components of the device are generated in the category of valid. Practicality of the device is measured based on the learning management sheet shown by the fulfillment of every aspect in the category of good and very well. The effectiveness of the device is incated by the fulfillment 3 of 4 effectiveness indicators defined. Such as: (The average percentage of classical completion of learning outcames test is more than 85%, (2) The fulfillment 7 of 9 categories of students activity, (3) all students responded positively by 100% of each of these aspects responded.